AN EFFECT OF PRODUCT QUALITY ON CUSTOMER SATISFACTION AT KFC FAST FOOD RESTAURANT BRANCH TITI KUNING - Aminuddin Aminuddin (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
Product quality is a product or service that is produced and provides a high-quality value to meet the needs of the community. As the fulfillment of community needs, customer satisfaction is one of the most important things in evaluating a product. The more satisfied customers are with the products used, the better the quality provided. This paper is entitled “The Effect of Product Quality on Customer Satisfaction at Fast Food Restaurants KFC Branch Titi Kuning, Medan". The background of this research is the interest of researchers to find out whether there is an effect of product quality on customer satisfaction at KFC fast-food restaurants. The purpose of this study was to see if there was an effect of product quality at KFC on customer satisfaction. The research method used by the researcher is an associative quantitative research method that aims to measure the effect of the independent variable on the dependent variable. To support the research, data were taken from product quality and customer satisfaction questionnaires. The population in this study was 30 customers of KFC Titi Kuning. The research data were analyzed using a simple linear regression model which resulted in the regression equation: Y = 21,915 + 0,534X. This study concludes that there is a significant effect between product quality on customer satisfaction at the KFC branch Titi Kuning of the Medan fast food restaurant, which means that the better the quality provided, the higher the level of customer satisfaction.